Tryptophan Metabolites in the Progression of Liver Diseases - Maria Reshetova; Pavel Markin; Svetlana Appolonova; Ismail Yunusov; Oksana Zolnikova; Elena Bueverova; Natiya Dzhakhaya; Maria Zharkova; Elena Poluektova; Roman Maslennikov; Vladimir Ivashkin (Biomolecules)
The aim of this study was to investigate the levels of various tryptophan metabolites in patients with alcoholic liver disease (ALD) and metabolic-associated fatty liver disease (MAFLD) at different stages of the disease. The present study included 44 patients diagnosed with MAFLD, 40 patients diagnosed with ALD, and 14 healthy individuals in the control group. The levels of tryptophan and its 16 metabolites (3-OH anthranilic acid, 5-hydroxytryptophan, 5-methoxytryptamine, 6-hydroxymelatonin, indole-3-acetic acid, indole-3-butyric, indole-3-carboxaldehyde, indole-3-lactic acid, indole-3-propionic acid, kynurenic acid, kynurenine, melatonin, quinolinic acid, serotonin, tryptamine, and xanthurenic acid) in the serum were determined via high-performance liquid chromatography and tandem mass spectrometry. In patients with cirrhosis resulting from MAFLD and ALD, there are significant divergent changes in the serotonin and kynurenine pathways of tryptophan catabolism as the disease progresses. All patients with cirrhosis showed a decrease in serotonin levels (MAFLDp = 0.038; ALDp < 0.001) and an increase in kynurenine levels (MAFLDp = 0.032; ALDp = 0.010). A negative correlation has been established between serotonin levels and the FIB-4 index (p < 0.001). The decrease in serotonin pathway metabolites was associated with manifestations of portal hypertension (p = 0.026), the development of hepatocellular insufficiency (p = 0.008) (hypoalbuminemia; hypocoagulation), and jaundice (p < 0.001), while changes in the kynurenine pathway metabolite xanthurenic acid were associated with the development of hepatic encephalopathy (p = 0.044). Depending on the etiological factors of cirrhosis, disturbances in the metabolic profile may be involved in various pathogenetic pathways.